Glial autoantibody prevalence in Chinese optic neuritis with onset after age 45: clinical factors for diagnosis - Song, Honglu; Chuai, Yucai; Yang, Mo; Zhou, Huanfen; Sun, Mingming; Xu, Quangang; Wei, Shihui (Frontiers in Immunology, 2023)
Purpose: As glial autoantibody testing is not yet available in some areas of the world, an alternative approach is to use clinical indicators to predict which subtypes of middle-aged and elderly-onset optic neuritis (ON) have manifested.This study was a single-center hospital-based retrospective cohort study.Middle-aged and elderly-onset ON patients (age > 45 years) who had experienced the first episode of ON were included in this cohort. Single-and multi-parametric diagnostic factors for middle-aged and elderly-onset myelin oligodendrocyte glycoprotein immunoglobulin-associated ON (MOG-ON) and aquaporin-4 immunoglobulin-related ON (AQP4-ON) were calculated.From January 2016 to January 2020, there were 81 patients with middleaged and elderly-onset ON, including 32 (39.5%) AQP4-ON cases, 19 (23.4%) MOG-ON cases, and 30 (37.0%) Seronegative-ON cases. Bilateral involvement (47.4%, P = 0.025) was most common in the MOG-ON group. The presence of other concomitant autoimmune antibodies (65.6%, P = 0.014) and prior neurological history (37.5%, P = 0.001) were more common in the AQP4-ON group. The MOG-ON group had the best follow-up best-corrected visual acuity (BCVA) (89.5% ≤ 1.0 LogMAR, P = 0.001). The most sensitive diagnostic factors for middle-aged and elderly-onset MOG-ON were 'follow-up VA ≤ 0.1 logMAR' (sensitivity 0.89), 'bilateral involvement or follow-up VA ≤ 0.1 logMAR' (sensitivity 0.95), 'bilateral involvement or without neurological history' (sensitivity 1.00), and 'follow-up VA ≤ 0.1 logMAR or without neurological history' (sensitivity 1.00), and the most specific factor was 'bilateral involvement' (specificity 0.81). The most sensitive diagnostic factors for middle-aged and elderly-onset AQP4-ON were 'unilateral involvement' (sensitivity 0.88), 'unilateral involvement or neurological history' (sensitivity 0.91), and 'unilateral involvement or other autoimmune antibodies' (sensitivity 1.00), and the most specific factor was neurological history (specificity 0.98).Based on our cohort study of middle-aged and elderly-onset ON, MOG-ON is less prevalent than AQP4-ON and Seronegative-ON. Using multiple combined parameters improves the sensitivity and negative predictive value for diagnosing middle-aged and elderly-onset MOG-ON and AQP4-ON. These combined parameters can help physicians identify and treat middle-aged and elderlyonset ON early when glial autoantibody status is not available.